Ushul Fiqh dan Tipologi Penelitian Hukum Islam - Sadari, Sadari (Al-aqidah | Jurnal Studi Islam, 2019)
This article integrates between the sacred text (nash) and reality (al-waqi '), as the most important form in understanding Islamic law. The text in the perspective asy-Syatibi has three ways of reading namely qira'ah salafiyyah, qira'ah ta'wiliyyah and qira'ah maqashidiyyah, which serves to search for maslahah. The concept of maslahah has three conditions that is indicated by the syara' argument for acceptance, indicated by the syara' argument to be rejected and shown by specific propositions for acceptance or rejection. Then on the third condition is processed again into two first, related maslahah which is not shown by a specific proposition justifying or canceling, but there is a nass that is in line with the maslahah, second, related maslahah not shown by certain propositions that cancel or justify, but maslahah is in line with the action syara', this is known as maslahah mursalah, which offers the momentum of law as a breakthrough discipline in understanding social phenomena, as the opening of the ijtihad door horizon. Through the science of ushul fiqh sourced from the as-Qur'an and as-Sunnah would certainly be able to answer the problematics throughout the ages. The strength of the methodology of ushul fiqh (qawaid ushuliyah) and the methodology of fiqh understanding (qawaid al-fiqhiyyah) will be the driving force in building Islamic self-image especially for the Indonesian nation. The new spirit of ushul fiqh methodologically and philosophically comprehensive becomes a necessity.